Accounting Provisioning Under the Expected Credit Loss Framework : IFRS 9 in Emerging Markets and Developing Economies - A Set of Policy Recommendations - Caruso, Ezio (World Bank, Washington, DC, 2021)
In 2009, the G-20 in London recommended that accounting standard setters, strengthen accounting recognition of loan-loss provisions by incorporating a broader range of credit information (G20 2009). In response, the International Accounting Standards Board (IASB) issued International Financial Reporting Standard 9 (IFRS 9) in July 2014, it became effective in 2018. This paper relies on a survey and bilateral meetings with prudential supervisors. This paper deals with the expected credit loss framework, with a particular focus on EMDEs. In 2020, EMDEs were facing challenges when dealing with IFRS 9 during the Coronavirus (COVID-19) pandemic, given the unprecedented reversals in capital flows as global risk appetite declined. EMDEs are coping with weaker health care systems and more limited fiscal space to provide support. Based on the experience of the surveyed countries and their reflections on challenges and potential remedies that they used while implementing the IFRS 9 accounting framework, the authors identified a set of high level policy recommendations for prudential supervisors in emerging markets and developing economies (EMDEs) willing to transition to IFRS 9. The paper is organized as follows: Section 2 presents the survey results; Section 3 presents policy recommendations for supervisory authorities in countries that implemented IFRS 9 as well as in countries that are still in the process of IFRS 9 implementation; and Section 4 offers conclusions.